Prosomeric Hypothalamic Distribution of Tyrosine Hydroxylase Positive Cells in Adolescent Rats - Bilbao, María G.; Garrigos, Daniel; Martinez-Morga, Marta; Toval, Angel; Kutsenko, Yevheniy; Bautista, Rosario; Barreda, Alberto; Ribeiro Do-Couto, Bruno; Puelles, Luis; Ferran, José Luis (Frontiers in Neuroanatomy, 2022)
Most of the studies on neurochemical mapping, connectivity, and physiology in the hypothalamic region were carried out in rats and under the columnar morphologic paradigm. According to the columnar model, the entire hypothalamic region lies ventrally within the diencephalon, which includes preoptic, anterior, tuberal, and mamillary anteroposterior regions, and sometimes identifying dorsal, intermediate, and ventral hypothalamic partitions. This model is weak in providing little or no experimentally corroborated causal explanation of such subdivisions. In contrast, the modern prosomeric model uses different axial assumptions based on the parallel courses of the brain floor, alar-basal boundary, and brain roof (all causally explained). This model also postulates that the hypothalamus and telencephalon jointly form the secondary prosencephalon, separately from and rostral to the diencephalon proper. The hypothalamus is divided into two neuromeric (transverse) parts called peduncular and terminal hypothalamus (PHy and THy). The classic anteroposterior (AP) divisions of the columnar hypothalamus are rather seen as dorsoventral subdivisions of the hypothalamic alar and basal plates. In this study, we offered a prosomeric immunohistochemical mapping in the rat of hypothalamic cells expressing tyrosine hydroxylase (TH), which is the enzyme that catalyzes the conversion of L-tyrosine to levodopa (L-DOPA) and a precursor of dopamine. This mapping was also combined with markers for diverse hypothalamic nuclei [agouti-related peptide (Agrp), arginine vasopressin (Avp), cocaine and amphetamine-regulated transcript (Cart), corticotropin releasing Hormone (Crh), melanin concentrating hormone (Mch), neuropeptide Y (Npy), oxytocin/neurophysin I (Oxt), proopiomelanocortin (Pomc), somatostatin (Sst), tyrosine hidroxilase (Th), and thyrotropin releasing hormone (Trh)]. TH-positive cells are particularly abundant within the periventricular stratum of the paraventricular and subparaventricular alar domains. In the tuberal region, most labeled cells are found in the acroterminal arcuate nucleus and in the terminal periventricular stratum. The dorsal retrotuberal region (PHy) contains the A13 cell group of TH-positive cells. In addition, some TH cells appear in the perimamillary and retromamillary regions. The prosomeric model proved useful for determining the precise location of TH-positive cells relative to possible origins of morphogenetic signals, thus aiding potential causal explanation of position-related specification of this hypothalamic cell type.